Treatment pattern and precision evaluation of diabetes mellitus therapy complications of chronic renal failure at RSUD Undata Palu - Dian Rahmawati (Farmasains : Jurnal Farmasi dan Ilmu Kesehatan, 2020)
Diabetes mellitus (DM) is a chronic metabolic disease or disorder characterized by high blood sugar levels accompanied by disorders of carbohydrate, protein, and lipid metabolism, which can produce chronic complications due to the inability to function insulin. Uncontrolled DM can be a risk factor for kidney failure. Abnormalities that occur in the kidneys of people with diabetes are characterized by microalbuminuria. This study aimed to determine the pattern and treatment of DM patients with Chronic renal failure or Chronic Kidney Disease (CKD) at Undata Hospital Palu, whether it is following the standard. This research is a descriptive cross-sectional study with retrospective data collection on medical records. Sampling was done using a total sampling technique with medical record data of thirty patients based on inclusion criteria. Based on the results of the study, the use of drugs in patients with DM complications of CKD was fast-acting insulin as many as twenty three people (79.3%) because insulin is the leading choice for DM patients with complications of CKD, especially in patients undergoing hemodialysis. Evaluation of treatment in patients with DM complications of CKD follows the standard treatment used as a reference. Insulin is the primary choice for diabetes mellitus patients with chronic renal failure complications, especially in patients undergoing hemodialysis.